Optimization of PID controller parameters in interconnected power system using index curve based technique - Surendiran, S. (Institute of Electrical and Electronics Engineers Inc., 2017)
In this paper, Performance Index Curve Based Optimization (PICBO) technique is proposed to optimize the parameters of PID controller for Interconnected Power System with the occurrence of 5 step load perturbation in area 1. The performance index considered for minimization is ITAE criterion. Importance of any interconnected power system is to provide a better quality of power to the consumers. For this reason, the parameters of PID controller are optimized by PICBO and the responses are analyzed in terms of settling time, peak overshoot and peak time. The results are compared with the existing results of Time Varying Acceleration Coefficients with Dominant Social Component Particle Swarm Optimization (TVACDSC PSO) technique. Finally, it is concluded with the identification of better optimization technique which provides solution for supply of better quality of power to consumers in an interconnected power system. © 2016 IEEE.